Local Wisdom-Based 4-On (Vision, Action, Passion, and Collaboration) Model in Competencies of Machining Technique in Vocational Secondary Schools - Haris Abizar; Moh Fawaid; Muhammad Nurtanto; Soffan Nurhaji; Solis Setiyani (Faculty of Engineering, Universitas Negeri Yogyakarta, 2021)
This study aims to identify teacher competency needs and develop a local wisdom-based 4-ON (vision, action, passion, and collaboration) model in the competencies of machining technique in vocational secondary schools. The 4-ON model is a way to examine the professionalism of teachers in vocational secondary schools. The type of study is research and development, using the Richey and Klein model. The subjects are 26 vocational teachers of machining techniques. The data collection uses questionnaires and documentation. The questionnaire instrument is declared valid by 3 experts in content and tested with reliable results with a value of 0.82. The data analysis is quantitative descriptive. The study of the research and development are: (1) the teacher need for 4-ON (vision, action, passion, and collaboration) 79.81% response, the implementation of the local wisdom in learning 78.13% response, and six competencies machining technique expertise 80.48% response; (2) the local wisdom-based 4-ON model in the competencies of machining technique goes through 3 stages, namely development, process, and output for a result the professional and competent teacher.